Varietal Comparison of F1 Hybrid and Elite Varieties of Sesame - Briatia, Xoxiong; Lochamyeu , Chanthavong; Jaisil, Prasit (Souphanouvong University Journal Multidisciplinary Research and Development, 2017)
Using hybrid variety is one of the ways to increase crop yield. Because some hybrid varieties will show they heterobeltiosis better than pure line varieties, this performance appeared only in some of agronomic traits i.e. number of seeds per capsule, length of capsule, width of capsule, plant height and number of capsules per plant. The objective of this study was to compared some of agronomic traits of F1 hybrid (KKU40) and 10 pure lines i.e. KKU1, KKU2, KKU3, UB1 (check variety), UB2, UB3, MK60, KU18, C-plus and Buri-Ram. The results showed that KKU40 (hybrid) had better agronomic traits than that UB1 (check variety) as well as the plant height was taller and the capsule length was also longer than UB1, respectively. Moreover, KKU40 increased more number of capsules per plant (155.8 capsules) and number of seed per capsule (78.3 seeds) than UB1 (119.5 capsules and 69.9 seeds), respectively. Conclusion that F1 hybrid showed better of agronomic traits than those of elite varieties.